PENGARUH PROMOTION MIX TERHADAP LOYALITAS PASIEN DI POLIKLINIK RSUD PANEMBAHAN SENOPATI BANTUL - Pambudi Pambudi; Susanto Susanto (Universitas Muhammadiyah Yogyakarta, 2012)
The emergence of new hospitals and the development of private hospitals lead to a competition. The hospital must maintain customer and seize the competitors’customers, so that the hospitals need to do a promotion. Promotion mix evaluation has not ever been done in RSUD Panembahan Senopati Bantul. The type of the study is a descriptive study, cross sectional design, and proportionate sampling stratified random sampling. The amount of population is 135 056 patients. The amount of sample is 100 people. It is a linear regression analysis test.The regression equation Y : 0,188 X1 + 0,196 X2 + 0,385 X3 + 0,174 X4. It is obtained from the t test promotion mix variable that partially effect on the loyalty of the clinic patients. The smallest value of p / t the largest count shows that the most influence on patient loyalty is a personal selling variable. F test results obtained from the simultaneous promotion mix variable (X) effect on patient loyalty variable (Y). Promotion mix variables partially effect on the loyalty of the clinic patients. The most dominant of promotion mix variables is the personal selling variable, promotion mix variables simultaneously influence the loyalty of Poliklinik RSUD Panembahan Senopati.